Improving holographic writing performance of photo‐orientable azobenzene polymers by molecular glasses. Issue 20 (12th July 2016) - Probst, Christian; Meichner, Christoph; Audorff, Hubert; Walker, Roland; Kreger, Klaus; Kador, Lothar; Schmidt, Hans‐Werner
ABSTRACT: Long‐term stable holographic volume gratings in azobenzene‐containing films have potential applications as forgery‐proof security features or in holographic data storage. However, azobenzene‐based polymer systems often lack sufficiently high writing speeds. Here, an approach to improve the holographic writing performance of photo‐orientable azobenzene‐containing polymers by blending with azobenzene molecular glasses is presented. The molecular glass enhances the photo‐plastification effect and, consequently, the writing speed. This concept of improving the holographic performance of photo‐orientable azobenzene polymers with azobenzene molecular glasses is demonstrated with a homopolymer and two block copolymers. In the azobenzene homopolymer, an addition of 10 wt % of the molecular glass leads to a doubling of the writing speed. Simultaneously, the long‐term stability of inscribed gratings is maintained. In case of the block copolymers, the molecular glass is present in the polystyrene matrix and accumulates in the azobenzene minority phase. Adding 5–10 wt % of molecular glass improves the writing speed of the azobenzene block copolymer by a factor of 3–4. An addition of 15 wt % of molecular glass to the block copolymer containing azobenzene and nonphotoactive mesogenic side groups reduces the writing time by a factor of 15 and the long‐term stability of the gratings is retained. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 2110–2117 Abstract : Azobenzene molecular glasses boost the holographic writing performance of photo‐orientable azobenzene polymers significantly. This approach is suitable for a homopolymer as well as block copolymers. A 15 times improvement of the holographic writing performance is achieved, maintaining the stability of the inscribed gratings.